2004
DOI: 10.1007/s11095-004-7683-5
|View full text |Cite
|
Sign up to set email alerts
|

Marine Alkaloid Polycarpine and Its Synthetic Derivative Dimethylpolycarpine Induce Apoptosis in JB6 Cells Through p53- and Caspase 3-Dependent Pathways

Abstract: These results indicate that all three MAPK signaling pathways are involved in the response of JB6 cells to treatment with polycarpines. Evidence also supports a proapoptotic role of the JNKs signaling pathway in vivo and clearly indicates that JNKs are required for phosphorylation of c-Jun, activation of p53, and subsequent apoptosis induced by polycarpines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…A plethora of evidence exists that p53 is involved in the chemopreventive effects of many natural compounds. For example resveratrol, epigallocatechin-3-gallate, caffeine, and many other cancer-preventive substances suppress normal cell transformation or induce antiproliferative effects with subsequent apoptosis in cancer cells through a p53-dependent pathway [43,45,[56][57][58][59][60][61][62][63][64][65][66][67]. To explore a possible mechanism of the cancer-preventive action of rhizochalin and analogs, we studied pro-apoptotic properties of rhizochalin and the effect of the compounds 1 or 3 on p53 transcriptional activation in JB6 Cl41 p53 cells stably expressing a luciferase reporter gene controlled by a p53 DNA binding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of evidence exists that p53 is involved in the chemopreventive effects of many natural compounds. For example resveratrol, epigallocatechin-3-gallate, caffeine, and many other cancer-preventive substances suppress normal cell transformation or induce antiproliferative effects with subsequent apoptosis in cancer cells through a p53-dependent pathway [43,45,[56][57][58][59][60][61][62][63][64][65][66][67]. To explore a possible mechanism of the cancer-preventive action of rhizochalin and analogs, we studied pro-apoptotic properties of rhizochalin and the effect of the compounds 1 or 3 on p53 transcriptional activation in JB6 Cl41 p53 cells stably expressing a luciferase reporter gene controlled by a p53 DNA binding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Using flow cytometry and the DNA laddering method, we showed that quinones 1 and 3 -14 induced apoptosis in JB6 Cl41 cells and MEFs. The tumor suppressor protein, p53, which is a part of the cell's emergency team and functions to negatively regulate cell growth following DNA damage, is often involved in apoptosis induced by various stimuli including chemopreventive agents and drugs (41)(42)(43)(44)(45). However, in our study quinones 1 and 3 -14 did not activate p53 but instead, most of the quinones studied demonstrated significant inhibition of p53 dependent transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…The JB6 P + Cl41 mouse epidermal cell line and its stable transfectants were cultured as described previously (9). The human lung H460, colon HCT-116, and skin melanoma SK-MEL-28 and SK-MEL-5 cancer cell lines were obtained by American Type Culture Collection and were cultured in monolayers at 37jC and 5% CO 2 in RPMI, McCoy's, and MEM, respectively, containing 10% FBS, 2 mmol/L L-glutamine, 100 units/mL penicillin, and 100 Ag/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%